2020
DOI: 10.3906/tar-1811-33
|View full text |Cite
|
Sign up to set email alerts
|

The effects of wheatgrass length on antioxidant activity and total phenolic content in wheatgrass (Triticum spp.)

Abstract: This study was carried out with the aim of determining the effects of wheatgrass lengths on antioxidant activity and total phenolic content of wheatgrass belonging to different cultivars (Triticum spp.) in laboratory conditions in 2017. When the wheat seedlings grown in plastic containers under soilless conditions reached three levels of wheatgrass length (5-6, 8-9, and 11-12 cm), the seedlings were cut from the root collar and dried in an oven. As a result of analysis of the dried material, it was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Absorbance values were recorded against the reference solution at 760 nm. Total phenolic contents were calculated with the calibration graph of gallic acid and gived as gallic acid equivalents (GAE), (mg GAE/g sample) [24,25,26,35,36,37,38].…”
Section: Quantification Of Total Phenolic Contents; Folin-ciocalteu Rmentioning
confidence: 99%
“…Absorbance values were recorded against the reference solution at 760 nm. Total phenolic contents were calculated with the calibration graph of gallic acid and gived as gallic acid equivalents (GAE), (mg GAE/g sample) [24,25,26,35,36,37,38].…”
Section: Quantification Of Total Phenolic Contents; Folin-ciocalteu Rmentioning
confidence: 99%
“…Since wheatgrass can be easily grown in home cultivation, the aim of this study was to determine the influence of genotypes and cuttings on the content of metabolites with the antioxidant properties in wheatgrass juice. Savsatli (2020) suggested that it is important to determine the appropriate cultivars M. Kristić et al: THE INFLUENCE OF VARIETY AND CUTTING ON THE WHEATGRASS ... for the industry. Moreover, the wild wheat relatives are rarely investigated in terms of their genetic potential for a secondary metabolite synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Common wheat (Triticum aestivum L. AABBDD, 2n = 6x = 42) is a hexaploid with a huge and complex genome [30][31][32]. This causes difficulties in the analysis of gene families and functions.…”
Section: Introductionmentioning
confidence: 99%